Real-world evidence of eteplirsen treatment effects in patients with Duchenne muscular dystrophy in the USA - Joel Iff; Yi Zhon; Edward Tuttle; Deepshekhar Gupta; Xander Paul; Erik Henricson (Becaris Publishing Limited, 2023)
Aim: To evaluate treatment effects of eteplirsen among patients with Duchenne muscular dystrophy. Methods: Using real-world claims and electronic medical record data, this retrospective comparative analysis assessed eteplirsen-treated and control cohorts matched by age, disease progression state, and pre-index period healthcare resource utilization. Poisson regression was used to evaluate eteplirsen effects on healthcare resource utilization outcomes. Results: Eteplirsen was associated with statistically significant reductions in rates of hospital encounters (31%), emergency room visits (31%), need for pulmonary management (33%), cardiac management (21%), tracheostomy (86%), and assisted ventilation (39%) versus the control group. Other assessed outcomes favored eteplirsen numerically but did not all reach statistical significance. Conclusion: Eteplirsen-treated patients had reduced rates of multiple healthcare resource utilization measures versus matched controls.